Indonesian Minister of Religion's New Policy Proposal: 1 Semester Pre-Marital Guidance - Louise, George (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Premarital guidance is a preventive measure in building family resilience and reducing divorce rates. The government, through its latest policy, requires one semester of premarital guidance for prospective brides and grooms. This policy aims to equip couples with a comprehensive understanding of household life, the rights and obligations of husband and wife, and skills in resolving family conflicts. This article examines the government's policy regarding one semester of premarital guidance, its implementation practices, and its goals and functions in forming harmonious and prosperous families. In its implementation, one semester of premarital guidance involves religious institutions, academics, and family law practitioners. The materials taught include aspects of marriage law, reproductive health, family psychology, and household economic management. Learning methods include lectures, interactive discussions, simulations, and case studies, in order to provide a deeper and more applicable understanding for prospective brides and grooms. Although this policy has significant benefits, challenges in its implementation include the readiness of human resources, infrastructure, and public awareness of the importance of premarital guidance. In general, the main objective of one semester of premarital guidance is to increase the readiness of couples in facing married life, reduce the risk of divorce, and create harmonious and quality families. The function of this guidance includes educational, preventive, and curative aspects, which help couples build effective communication, resolve conflicts wisely, and understand each other's roles in the family. With this guidance, it is hoped that couples will have a strong foundation in living their married life, so that they can create a happy and prosperous family.